Analysis of Coupling Co-Ordination between Intensive Sea Use and the Marine Economy in the Liaoning Coastal Economic Belt of China - Xuefei Liu; Lina Ke; Hanyue Zhuang; Xiaoyu Yang; Nanqi Song; Song Wang (Complexity)
At present, there are few relevant studies on the intensive sea use, and few scholars have provided qualitative and quantitative research examples on the interaction and interaction coupling relationship between intensive sea use and the marine economy. This study constructs comprehensive evaluation indicator systems using the Liaoning Coastal Economic Belt as the research object. The set pair analysis method is used to obtain comprehensive results, and the coupling coordination degree model is employed to carry out an in-depth analysis of the spatiotemporal characteristics of the interaction between intensive sea use and the marine economy. The results show the following. (1) The six cities in the Liaoning Coastal Economic Belt exhibited a fluctuating upward trend in the composite index for intensive sea use, but the intensive sea use level differed among the cities. The intensive sea use level of Huludao was the lowest among the six cities. (2) All cities in the Liaoning Coastal Economic Belt witnessed an upward trend in the marine economy development index, and the gaps between the cities gradually narrowed. The marine economy development index was ranked from top to bottom as follows: Jinzhou, Panjin, Dalian, Yingkou, Dandong, and Huludao. (3)The coupling coordination degree between intensive sea use and marine economy development was relatively stable in Dalian, Jinzhou, Yingkou, and Panjin, ranging approximately from 0.76 to 0.96, which indicates that the four cities witnessed good coordination between sea area utilization and marine economy development. The coupling coordination degree of Dandong and Huludao were relatively low, and Huludao consistently witnessed a low value.